Examination Of Blood Group and Rhesus in Banyuhurip Village, Cibeureum Village - Regina , Gelfira Dewi; Handayani, Hani (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Knowing blood type has many benefits, including facilitating forensic identification, for transfusion purposes, as data contained in ID cards, driving licenses, and other identity cards. The conclusion of the observation stated that most of the people did not know their blood type, so a blood group check was carried out in Banyuhurip Village, Cibeureum Village. The examination was followed by 128 people with an age range of 7-65 years. The results of the examination showed that 40 people (31%) had blood type A, 24 people (19%) had blood type B, 10 people (8%) had blood type AB, and 54 participants (42%) had blood type O. All participants were rhesus positive (+) (100%). The sex distribution of the participants of the blood group test is 50 people (39%) are male and 78 people (61%) are female.